2016
DOI: 10.1039/c5fo01338k
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol modulates intestinal morphology and HSP70/90, NF-κB and EGF expression in the jejunal mucosa of black-boned chickens on exposure to circular heat stress

Abstract: The aim of this study was to investigate whether supplementation with resveratrol could alleviate intestinal injuries and to explore how resveratrol regulates heat shock protein (HSP)70, HSP90, nuclear factor kappa B (NF-κB) and epidermal growth factor (EGF) expression in the jejunal mucosa of black-boned chickens under circular heat stress. A total of 300 black-boned chicks of 42-d-old were randomly assigned to five treatment groups. The positive control chickens were kept in a normal-temperature (NT, 24 ± 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
99
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(104 citation statements)
references
References 43 publications
5
99
0
Order By: Relevance
“…Liu et al. (, ) observed that heat stress improved HSPs mRNA expression, and resveratrol suppresses HSPs expression under heat stress in black‐bone chickens. Rhoads, Baumgard, Suagee, and Sanders () reported that heat shock proteins (HSPs) may enhance insulin function via improved insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al. (, ) observed that heat stress improved HSPs mRNA expression, and resveratrol suppresses HSPs expression under heat stress in black‐bone chickens. Rhoads, Baumgard, Suagee, and Sanders () reported that heat shock proteins (HSPs) may enhance insulin function via improved insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, increased crypt depth in poultry is associated with small intestine damage due to stress stimuli (e.g. heat stress), which negatively influence functions in digestion and absorption [39].…”
Section: Discussionmentioning
confidence: 99%
“…EGF, as a polypeptide growth factor, has a close relationship with intestinal growth regarding promoting cell proliferation (Chan et al 2015) and the restoration of damaged epithelium (Liu et al 2016a). Xu et al (2015) demonstrated that EGF maintains the structural integrity and function of the small intestine in early-weaned piglets.…”
Section: Discussionmentioning
confidence: 99%